2020
DOI: 10.3390/en13061371
|View full text |Cite
|
Sign up to set email alerts
|

Improved Energy Management in an Intermittently Heated Building Using a Large Broiler House in Central Europe as an Example

Abstract: This paper deals with the problem of rational energy management in an intermittently heated broiler house. The aim was to evaluate the energy amount necessary to heat up the building floor for the production cycle, preceded by a technological interruption of varying length. The scope of studies included the indoor and outdoor air temperature measurements and the soil temperature measurements under the building floor. The results of field tests allowed computer simulations to be carried out in the WUFIplussoftw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…A similar approach was used in this study (constant dampness level in the ground profile). The applied WUFI ® plus calculation tool was used repeatedly for non-stationary analyses, taking the coupling between the building and the ground into account [10,27,[30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach was used in this study (constant dampness level in the ground profile). The applied WUFI ® plus calculation tool was used repeatedly for non-stationary analyses, taking the coupling between the building and the ground into account [10,27,[30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The location of the building and the prevailing climate primarily determine the energy performance of buildings and the requirements placed on them, from the perspective of thermal protection and energy efficiency [25]. The specific mode of operation of agricultural buildings, especially cyclic use, can be a positive feature in terms of the possibility of technological and functional modifications [14,26,27]. The results of analyzing the influence of location on the energy management of the studied buildings showed that the external climate significantly determined the amount of energy expenditure for heating purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The significant influence of ventilation on shaping the interior microclimate was demonstrated in the work of Verboven et al [13]. The subject of broiler houses was also discussed in recent years, when the results of the impact of the length of the technological break between production cycles on the energy of the building were developed [14]. Martin and Canas [15] analyzed the benefits of storing wine in recessed cellars.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural buildings used periodically allow numerous technological and operational modifications. They can contribute to rational management of energy necessary to maintain a given building type [28,29]. Current state of knowledge shows that the share of the ground in the total energy balance of residential and industrial buildings is about 5-10% [17].…”
Section: Discussionmentioning
confidence: 99%